Optimizing Conditions to Combat Antibiotic Resistance in Pathogenic Bacteria: Mengoptimalkan Kondisi untuk Memerangi Resistensi Antibiotik pada Bakteri Patogen - Adawia Fadhel Abbas (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Antimicrobial resistance (AMR) is a significant adaptive trait that allows pathogenic bacterial subpopulations to out-compete and out-survive their microbial neighbors and overcome host defenses. Specific Background: Despite extensive research, the influence of various environmental parameters on antibiotic sensitivity in pathogenic bacteria remains underexplored. Knowledge Gap: There is limited understanding of how temperature, pH, bacterial inoculum volume, and culture medium amount affect the antibiotic resistance of both gram-negative and gram-positive bacteria. Aims: To investigate the effects of these parameters on the antibiotic sensitivity of four standard laboratory strains: Escherichia coli, Proteus spp., Klebsiella spp., and Staphylococcus aureus. Results: Our findings indicate imipenem exhibited the highest sensitivity, with percentages varying significantly based on temperature (92% at 35-39°C), pH (83% at pH 6-8), inoculum volume (42% at 0.1-1.0 μL), and medium volume (67% at 15-35 ml). Conversely, antibiotics such as Piperacillin, Amoxicillin, Erythromycin, Tetracycline 30, and Cephalexin showed high resistance, with Tetracycline 10 being the most resistant. Novelty: This study highlights the significant impact of environmental conditions on bacterial antibiotic resistance, emphasizing the need for tailored antibiotic use based on specific bacterial characteristics and growth conditions. Implications: The results suggest that optimizing environmental parameters can enhance antibiotic efficacy and inform better clinical practices to combat AMR, thus improving treatment outcomes for bacterial infections. Highlights: Parameter Influence: Temperature, pH, inoculum, medium amount affect antibiotic sensitivity. Highest Sensitivity: Imipenem most effective across conditions. Tailored Use: Optimize conditions for better antibiotic efficacy. Keywords: Antimicrobial resistance, bacterial sensitivity, environmental parameters, Imipenem, pathogenic bacteria